MicroRNAs in neuronal function and dysfunction - Im, Heh-In (2012)
MicroRNAs (miRNAs) are small noncoding RNA transcripts expressed throughout the brain that can regulate neuronal gene expression at the post-transcriptional level. Here, we provide an overview of the role for miRNAs in brain development and function, and review evidence suggesting that dysfunction in miRNA signaling contributes to neurodevelopment disorders such as Rett and fragile X syndromes, as well as complex behavioral disorders including schizophrenia, depression and drug addiction. A better understanding of how miRNAs influence the development of neuropsychiatric disorders may reveal fundamental insights into the causes of these devastating illnesses and offer novel targets for therapeutic development.